2006
DOI: 10.1002/bdrb.20068
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke and sudden infant death syndrome: a review

Abstract: Environmental tobacco smoke (ETS), containing the developmental neurotoxicant, nicotine, is a prevalent component of indoor air pollution. Despite a strong association with active maternal smoking and sudden infant death syndrome (SIDS), information on the risk of SIDS due to prenatal and postnatal ETS exposure is relatively inconsistent. This literature review begins with a discussion and critique of existing epidemiologic data pertaining to ETS and SIDS. It then explores the biologic plausibility of this ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 92 publications
0
27
0
Order By: Relevance
“…The role of tobacco smoke exposure in SIDS has been the subject of several recent reviews (Adgent, 2006;Mitchell and Milerad, 2006;Fleming and Blair, 2007). There have been over 60 studies of the relationship between maternal smoking and secondhand smoke exposure during pregnancy and the risk of SIDS.…”
Section: Sudden Infant Death Syndromementioning
confidence: 99%
“…The role of tobacco smoke exposure in SIDS has been the subject of several recent reviews (Adgent, 2006;Mitchell and Milerad, 2006;Fleming and Blair, 2007). There have been over 60 studies of the relationship between maternal smoking and secondhand smoke exposure during pregnancy and the risk of SIDS.…”
Section: Sudden Infant Death Syndromementioning
confidence: 99%
“…Most of these substances are toxic or carcinogen, and many studies demonstrated their correlation with several chronic diseases and different kind of cancers (IARC, 2012;USDHHS, 2014). Thus, ETS exposure generates a great concern for public health, especially when it occurs during infancy and childhood for two reasons: (1) children are the most susceptible population to the harmful health effects associated to ETS exposure (Adgent, 2006;Asomaning et al, 2008;Cheraghi and Salvi, 2009;Muller, 2007), and (2) the early initiation of exposure may facilitate, later in life, the onset of ETS-related diseases characterized by a prolonged latency (Cheraghi and Salvi, 2009;Svanes et al, 2004). The most important contributions to ETS exposure for a child are given by the presence and the smoking habits of cohabiting smokers in her/his domestic environment (McNabola and Gill, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Following the worldwide campaign to promote supine sleep in infants, perinatal environmental tobacco smoke (ETS) appears as the main preventable risk factor for sudden infant death syndrome (SIDS) (Adgent, 2006;Liebrechts-Akkerman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%